Do small spores disperse further than large spores?. Issue 6 (1st June 2014) - Norros, Veera; Rannik, Üllar; Hussein, Tareq; Petäjä, Tuukka; Vesala, Timo; Ovaskainen, Otso
Abstract : In species that disperse by airborne propagules an inverse relationship is often assumed between propagule size and dispersal distance. However, for microscopic spores the evidence for the relationship remains ambiguous. Lagrangian stochastic dispersion models that have been successful in predicting seed dispersal appear to predict similar dispersal for all spore sizes up to ∼40 μm diameter. However, these models have assumed that spore size affects only the downwards drift of particles due to gravitation and have largely omitted the highly size‐sensitive deposition process to surfaces such as forest canopy. On the other hand, they have assumed that spores are certain to deposit when the air parcel carrying them touches the ground. Here, we supplement a Lagrangian stochastic dispersion model with a mechanistic deposition model parameterized by empirical deposition data for 1–10 μm spores. The inclusion of realistic deposition improved the ability of the model to predict empirical data on the dispersal of a wood‐decay fungus (aerodynamic spore size 3.8 μm). Our model predicts that the dispersal of 1–10 μm spores is in fact highly sensitive to spore size, with 97–98% of 1 μm spores but only 12–58% of 10‐μm spores dispersing beyond 2 km in the simulated range of wind and canopy conditions. Further, excluding the assumption of certain deposition at the ground greatly increased the expected dispersal distances throughout the studied spore size range. Our results suggest that by evolutionary adjustment of spore size, release height and timing of release, fungi and other organisms with microscopic spores can change the expected distribution of dispersal locations markedly. The complex interplay of wind and canopy conditions in determining deposition resulted in some counterintuitive predictions, such as that spores disperse furthest under intermediate wind, providing intriguing hypotheses to be tested empirically in future studies.